Carrier-free nanomedicines for cancer treatment. (April 2022) - Liu, Li-Han; Zhang, Xian-Zheng
Abstract: The last decade witnessed the great advances in the development of nanomedicines. As a kind of attractive nanomedicine, carrier-free nanomedicines received extensive investigations because of their high biosafety, high drug loading capacities, simple drug compositions and simplified synthetic procedures. Extensive efforts have been made to exploit more excipients and therapeutic agents, new self-assembly methods and therapeutic mechanisms to expand the scope of carrier-free nanomedicines with enhanced therapeutic performance. In this review, we summarized the research progress of carrier-free nanomedicines with practical applications in cancer therapy. Carrier-free nanomedicines were classified into three kinds, including free drugs, prodrugs and non-drug agents based carrier-free nanomedicines. These carrier-free nanomedicines were introduced in detail according to their drug compositions, assembly and antitumor applications. The current clinical translation situation and safety of carrier-free nanomedicines were also summarized. The outlooks were included in the conclusion section to discuss the existing challenges on the future development and clinical application of carrier-free nanomedicines.